A feasibility study of reducing scour around monopile foundation using a tidal current turbine. (15th January 2021) - Yang, Bo; Wei, Kexiang; Yang, Wenxian; Li, Tieying; Qin, Bo
Abstract: The monopile foundations of offshore wind turbines in shallow waters are susceptible to be affected by tidal scour, which takes away the sand and soil around the monopiles and poses a serious threat to the safety of the turbines. To mitigate this issue, much effort has been made previously. However, all of the existing protective measures do not have added value other than scouring mitigation. In view of this, a new scour mitigation measure that utilizes tidal current turbine (TCT) is investigated in this study, which can not only reduce the scour around the wind turbine foundation but can also generate clean power simultaneously. In the research, the proposed method is studied by using a combined numerical simulation and laboratory testing approach. Both numerical calculation and experimental results have shown that a TCT installed in front of the monopile foundation of an offshore wind turbine does have a positive role in reducing the scour around the foundation when it generates electricity in the meantime. Moreover, the contribution of the TCT to scour reduction can be further improved through optimizing its installation position in front of the wind turbine. Highlights: A new scour mitigation measure that utilizes tidal current turbine (TCT) is proposed. The seabed erosion around the monopile foundation of an OWT can be reduced by a TCT installed in front of it. The TCT will reduce seabed erosion effectively when it is installed at an optimal position.